NEWZKIOSK.COM - Abdelmonem, Mohamed Ahmed (Universiti Teknologi Petronas, 2011)
As we are a part of a world full of news, every second there is something happening in the world. IT major players companies did a lot of effort helping the users to find news and follow them by making new technologies like Really Simple Syndication (RSS), online news portals, and SMS subscriptions. Each of those has many problems. For example, RSS could send more than 12,000 emails in less than 8 hours. SMS could help the user to follow only one source of news and the user has to pay for it. NEWZKIOSK IS offering the main headlines from the most famous news sources (CNN, BBC, NYT, Reuters). RSS and WordPress platform will allow Newzkiosk to offer the users the most compatible news portal over the web, less advertisements for more users' satisfaction and convenience.